PENGARUH TEMA DOMINAN PESAN DAKWAH DIGITAL TERHADAP AKUN INSTAGRAM @FSLDK_SULTRA - Rizal, Ahmad; La Tarifu, La Tarifu; Ridwan, Harnina (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2020)
The development of communication technology has progressed very rapidly, the delivery of messages can be done so quickly and with a variety of application media choices. One of them is the Instagram account @fsldk_sultra utilizing Instagram as a medium for delivering da'wah messages to his followers. The purpose of this study was to determine the effect of the dominant theme of digital propaganda messages on the Instagram account @fsldk_sultra. This study uses an explanatory content analysis method with a quantitative approach to get a complete picture of a message while testing certain hypotheses. This research was conducted in four stages, namely: data collection, compilation of the preaching message theme categories presented by Wahidin Saputra, reliability testing, and data calculation using koding sheets filled by three predetermined koding people. There are three categorizations of the unit of analysis in this study, namely the message of preaching aqidah, sharia and morals. The results showed a high relationship between the influence of the dominant theme on the @fldk_sultra instagram account, namely on the da'wah message with the shari'a theme 60.72%. While the rest is aqidah message 30.18% and morals 9.09%.Â Keywords: Da'wah Message;Instagram Account;Content Analysis